Sulfur modulates yield and storage proteins in soybean grains - Ibanez, Thiago Bergamini [UNESP]; Melo Santos, Luiz Felipe de [UNESP]; Lapaz, Allan de Marcos [UNESP]; Ribeiro, Igor Virgilio [UNESP]; Ribeiro, Filipe Virgilio [UNESP]; Reis, Andre Rodrigues dos [UNESP]; Moreira, Adonis; Heinrichs, Reges [UNESP] (Univ Sao Paolo, 2021)
This study evaluated the nutritional quality, yield, and storage protein modulation in soybean grains in response to levels and sources of sulfur (S) in a dystrophic Ultisol. We used five levels of S (0, 50, 100, 150 and 200 mg kg(-1)) and four sources of S (elemental S pastille-ESPA, gypsum - GY, gypsite - GI and elemental S powder - ESPO). Plants treated with 50 mg kg(-1) of GY, GI, and ESPO and 200 mg kg(-1) of ESPA had the largest grain yield values. Low S supply resulted in lower yields for all S sources tested. Sulfur deficiencies were observed at all levels for ESPA, resulting in lower concentrations of globulin and higher concentration of glutelin and albumin in the grains, possibly because the S content in the leaf was below the range adequate for soybean, leading to in lower yield values. In general, the application of S sources (GY, GI, and ESPO) increased all protein fractions. The results show that proper application of S is essential to optimize soybean yield and increase storage proteins in the grains. The granulometry of ESPA and ESPO fertilizers was a key factor for the availability of S to soybean plants. This study presents relevant information on S fertilization of soybeans, which could provide better grain nutritional quality and increased storage proteins with benefits to animal health.
Keywords: Glycine max; plant nutrition; elemental sulfur; sulfate